Morbidity and mortality in hospitalised neonates in central Vietnam. (9th March 2015) - Tran, Hoang T.; Doyle, Lex W.; Lee, Katherine J.; Dang, Na M.; Graham, Stephen M.
Abstract Aim This study explored neonatal morbidity and mortality in hospitalised patients in central Vietnam and risk factors associated with mortality. Methods We conducted a prospective cohort study of all newborn infants (<28 days) hospitalised in a neonatal unit over a 1‐year period and followed until discharge. The main outcome measures were case fatality rate and the rate of different clinical diagnoses. Results There were 2555 admissions during the study period. The leading primary causes of admissions were infections (41%), haematological problems such as jaundice (23%) and prematurity and its complications (18%). The overall case fatality rate was 8.6%, and it was 59% among very low‐birthweight (<1500 g) neonates. Mortality was inversely associated with birthweight and gestational age. Of the 220 deaths, 57% occurred within the first 7 days of life. Although the causes of death were often multifactorial, the leading primary causes were infections (32%), prematurity and its complications (25%), birth defects (24%) and birth asphyxia (6%). Risk factors associated with death were being outborn, early gestational age, small for gestational age, confirmed sepsis and birth defects. Conclusion Mortality rates were high among hospitalised neonates in central Vietnam, and this paper suggests interventions that might improve outcomes.